2023
DOI: 10.1007/s10103-023-03764-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intravascular photobiomodulation on cognitive impairment and crossed cerebellar diaschisis in patients with traumatic brain injury: a longitudinal study

Abstract: The association between intravascular photobiomodulation (iPBM) and crossed cerebellar diaschisis (CCD) and cognitive dysfunction in patients with traumatic brain injury (TBI) remains unknown. We postulate that iPBM might enable greater neurologic improvements. The objective of this study was to evaluate the clinical impact of iPBM on the prognosis of patients with TBI. In this longitudinal study, patients who were diagnosed with TBI were recruited. CCD was identified from brain perfusion images when the uptak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 58 publications
(58 reference statements)
0
5
0
Order By: Relevance
“…Despite these benefits, ILIB has not been used to treat migraine. Our previous case report showed that ILIB could improve perfusion of the contralateral cerebellum during diaschisis after an ischemic stroke event [ 17 ], or traumatic brain injury [ 14 ], and improve sleep quality in patients with musculoskeletal pain [ 18 , 19 ]. In the current study, we demonstrated ILIB-associated improvements in pain, cognition, disability, insomnia, and rCBF in patients with migraine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite these benefits, ILIB has not been used to treat migraine. Our previous case report showed that ILIB could improve perfusion of the contralateral cerebellum during diaschisis after an ischemic stroke event [ 17 ], or traumatic brain injury [ 14 ], and improve sleep quality in patients with musculoskeletal pain [ 18 , 19 ]. In the current study, we demonstrated ILIB-associated improvements in pain, cognition, disability, insomnia, and rCBF in patients with migraine.…”
Section: Discussionmentioning
confidence: 99%
“…Laser power intensity was 0.51–2.55 W/cm 2 , energy was 3.6–18 J, and energy density was 1836.73–9183.67 J/cm 2 . Power intensity was adjusted based on the patient’s clinical responses [ 14 ]. Specifically: (1) Initial Dosage Setting Based on BMI: The starting output dosage for the laser was determined by the patient's body mass index (BMI).…”
Section: Methodsmentioning
confidence: 99%
“…This approach ensured that almost 100% of the total blood volume was irradiated during each 60 min session. The mean transit time from the regional arm to the brain was less than 30 s, indicating that all the blood was likely irradiated during each session [ 35 ]. Although the iPBM treatment required the insertion of a catheter into a vein, it was generally considered a minimally invasive procedure because it did not require any incisions or major surgical interventions.…”
Section: Methodsmentioning
confidence: 99%
“…1 | is extremely wide and includes neurological [1-3, 8, 17, 31, 39], traumatological and orthopedic [5,48], ophthalmological pathology [20], a number of psychiatric diseases [6,9,11,21,29,33] and others. In addition, there is information in the literature about the positive experience of using PBM technology in dentistry [37], regenerative medicine (in particular, for the treatment of wounds of various origins [7], the treatment of alopecia [24] and stimulation of osteogenesis [18]) and post-traumatic conditions [10,23,30,[34][35][36], sports medicine [4,19,28] and even the treatment of some forms of cancer [25]. Such an extensive range of clinical applications of the technology is due to the diverse effects of photobiomodulation, however, for a full understanding of the pathogenetic mechanisms of its action and targeted inclusion of the method in clinical recommendations, further disclosure of both fundamental aspects of the problem and large-scale clinical testing of the technology in various categories of patients is necessary.…”
Section: The Scope Of Photobiomodulationmentioning
confidence: 99%
“…A separate area of application of the technology is post-stroke rehabilitation, which promotes accelerated recovery of speech functions and verbal skills [2]. A number of publications are devoted to the effectiveness of using the method in the treatment of patients with traumatic brain injury [10,23,30,[34][35][36]38]. The authors note a decrease in the severity of headache, sleep disorders, accelerated normalization of cognitive functions, elimination of symptoms of depression, anxiety and irritability.…”
Section: Possibilities Of Photobiomodulation In Neurological and Psyc...mentioning
confidence: 99%